KNOWLEDGE, ABILITIES, SKILLS ON PSYCHOLOGY OF RELIGION - AS THE MAIN FACTORS OF FORMATION OF PSYCHOLOGICAL IMMUNITY (American Journal of Research in Humanities and Social Sciences, 2024)
The article is devoted to the analysis of the concept of psychological immunity in the context of modern ideological challenges and the role of religion in its formation. The influence of globalisation and information attacks on the psychological immunity of young people is investigated, stressing the importance of integrating spiritual and moral values of Islam into the educational process. The author proposes a comprehensive approach to the development of psychological immunity, including theoretical training, practical activities and active participation in public life, with an emphasis on maintaining adherence to the principles of secularism and mutual understanding between different religious and cultural traditions.